Teacher Agency for Change and Development in Higher Education: A Scoping Literature Review - Ngô, Công Lem (2024)
This paper reviews 42 empirical studies on tertiary educators’ professional agency, identifying five key practices: pedagogical innovation, research engagement, professional learning, curriculum change, and maintaining well-being. Teacher agency has been variably conceptualized as being influenced by internal and external factors, such as curriculum reforms, social relationships, personal identities, beliefs, and emotions. Individual capacities and enactment strategies, along with contextual conditions like leadership and support, are crucial for effective teacher agency. Implications for policy-making and teacher professional development to foster effective change are discussed, with a conceptual framework proposed for investigating teacher agency holistically in its complexity.